Dampak Devaluasi Yuan Pada 11 Agustus 2015 Terhadap Abnormal Return Dan Abnormal Trading Volume Activity Saham Yang Tercatat Di Jakarta Islamic Index JII) - Windiya Saputri; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
Government-related announcement is one of the determinants that potentially affect capital market. This research aims to see the reaction of stock market to Yuan Devaluation on August, 11 2015. The market reaction in this study is indicated by the presence of abnormal retun and abnormal trading volume activty. The approach taken in this research is the quantitative approach with event study method by using one sample t-test and paired sample t-test analysist. The variables in this research are Yuan Devaluation, AAR, and AATVA. The issuers observed in this research are stock listed on JII during the period of study. Results showed that stock listed on JII reacted to Yuan Devaluation, that is showed by significant results both in the AAR and AATVA, which means Yuan Devaluation bears valuable information for investor.